PERAN PARTAI POLITIK DALAM AKOMODASI KEPENTINGAN DI FRAKSI DPRD KOTA PALANGKA RAYA - Margaretha Novi Kristiani; Ester Sonya Ulfaritha Lapalu (Jurusan Ilmu Pemerintahan, 2018)
This study aims to describe and analyze the role of political parties in accommodation interests in the fraction of DPRD Palangkaraya City and see the inhibiting factors and supporting the role of political parties in accommodation interests in the fraction of DPRD Kota Palangka Raya. The research method used qualitative descriptive research. Data analysis techniques conducted in this research is through data collection, data reduction, data presentation and verification. This research uses the function of political party with Sastroadmodjo theory. The indicators include the function of articulation of interests, the function of interest aggregation, the functions of policy making, the function of policy implementation and the function of judgment policy which is done by observation, interview and documentation. The results of this study indicate that the role of political parties in the accommodation of interest in the fraction of DPRD Palangkaraya in the articulation function of the faction interests in the DPRD absorbs and collects the aspirations of the community through the DPRD Resres and in the function of interest aggregation, the DPRD fractions to sort out and prioritize the demands or problems which is dominant, in the implementation of the policy making function, the fraction is expected to form a policy in favor of the people in terms of the function of the policy implementation of the fraction in charge of the Regional Regulatory Body first socialize the local regulation to the community and in the judicial function of the DPRD DPRD Palangka Raya Satpol PP as enforcer of regional regulation to discipline society that violate the rules. Suggestions on this research are expected to the Executive can equate the priority programs together with the Legislature and the community is expected to play an active role in submitting demands or suggestions to the government. Keywords: Role, Political Party, Accommodation Interests, Faction, DPRD